Connecting the Dots: Haptic Imagery's Sequential Impact via Serial Mediation in Social Commerce Applications - Chong, S.; Basha; Lim, X. (International journal of business science & applied management, 2024)
By integrating the Theory of Interactive Media Effects (TIME) and flow theory, this research investigates the influence of haptic imagery on users' experiences and behavioural intentions within the context of Social Commerce Applications (SCAs). This research delves into the mediating role of immersion and the intricate serial mediation dynamics involving immersion and social media fatigue, elucidating their role in the link between haptic imagery and users' continuance intention. A purposive sampling technique was employed to gather data from 410 users of SCAs in Malaysia via offline and online data collection methods. The collected data underwent analyses using partial least squares-structural equation modelling (PLS-SEM). The findings revealed that haptic imagery was positively associated with immersion, negatively associated with social media fatigue, and positively associated with continuance intention among users of SCAs. Immersion emerges as a crucial mediator, sequentially linking haptic imagery to social media fatigue and subsequently to continuance intention. The study pioneers research into the influence of haptic imagery in the context of SCAs, contributing to the underexplored research gaps in social commerce continuance literature. The study unravels the intricate relationships between haptic imagery, user experiences, and behavioural intentions, shedding light on the serial mediation mechanisms in shaping users' continuance intention. This pioneering approach facilitates a novel understanding of technology-mediated user behaviour.